Pengembangan Instrumen Ranah Kognitif pada Pokok Bahasan Fluida Statis SMA/MA - Mustari, Mukarramah (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2016)
This study aims to: 1) Develop Instrument Domains Cognitive at Static Fluid material in SMA / MA, 2) determine the validity of the instrument of cognitive tests on the static fluid material, 3) determine the reliability of cognitive principal static fluid discussion, 4) determine the level of difficulty of the cognitive tests on  the static fluid material, 5) determine distinguishing cognitive test on static fluid material. The result products include cognitive aspects such instruments multiple choice tests and essay tests.Instrument developed on cognitive aspects in the form of multiple choice tests and a description to the extent of competence Bloom C1 to C6 on the material of Static Fluid. The Design of this study is used the development procedure Reasearch and Depelopment (R & D) from Borg and Gall adopted by Sugiono ie; up to the stage seven form consisting of: the potential and problems, data collection, product design, design validation, design revisions, product trials, product revision. The data collecting is obtained from the results of expert validation instrument, the response of teachers, and product trials, and then analyzed by quantitative descriptive. The results of the analysis of the development of the instrument can be concluded that the cognitive instruments on the material of static fluid SMA / MA is excellent to be used by teachers in the assessment of competence of learners.Penelitian Pengembangan Instrumen Ranah Kognitif pada Pokok Bahasan Fluida Statis SMA/MA Ini dilakukan bertujuan;1) Mengembangkan Instrumen Ranah Kognitif pada Pokok Bahasan Fluida Statis SMA/MA, 2) mengetahui validitas instrumen tes kognitif pokok bahasan fluida statis, 3) mengetahui reliabilitas kognitif pokok bahasan fluida statis, 4) mengetahui tingkat kesukaran tes kognitif pokok bahasan fluida statis, 5) mengetahui daya pembeda tes  kognitif pada pokok bahasan fluida statis.Produk yang dihasilkan meliputi instrumen aspek kognitif berupa tes pilihan jamak dan tes uraian.Instrumen yang dikembangkan pada aspek kognitif berupa tes pilihan jamak dan uraian sampai pada taraf kompetensi Bloom C1 sampai dengan C6 pada pokok bahasan Fluida Statis. Desain Penelitian ini menggunakan prosedur pengembangan Reaserch and Depelopment( R&D ) dari Borg and Gall yang diadopsi oleh Sugiono yakni sampai pada tahap ke tujuh berupa yang terdiri dari: potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi desain, uji coba produk,revisi produk. Pengumpulan data diperoleh dari hasil validasi ahli instrumen, respon guru, dan uji coba produk, kemudian dianalisis dengan deskriptif kuantitatif. Hasil analisis pengembangan instrumen dapat disimpulkan bahwa instrumen ranah kognitif pada pokok bahasan fluida statis SMA/MA sangat baik untuk digunakan oleh guru dalam penilaian kompetensi peserta didik